2017
DOI: 10.12973/eurasia.2017.00945a
|View full text |Cite
|
Sign up to set email alerts
|

Use of Assistive Technology for Teaching-Learning and Administrative Processes for the Visually Impaired People

Abstract: This study aims to examine how technology used in the Cyprus Turkish Blind Association assisted the teaching-learning and administrative processes for the visually impaired. Qualitative research techniques were used for data collection and analysis. This study is a case study that aims to examine how the technology used in the association facilitated the teaching-learning and administrative processes for the visually impaired people. The study also found that with the assistance of technology the participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
(9 reference statements)
0
8
0
1
Order By: Relevance
“…Studies about the use of mobile devices for children with SEND dates to 2000 in Turkey (Silman, Yaratan, & Karanfiller, 2017). For instance, a study conducted with parents of children with SEND showed that parents have positive attitudes towards using new tools and mobile applications (Kuzu, Cavkaytar, Odabaşı, Erişti, & Çankaya, 2014).…”
Section: Mobile Education Technologies In Turkeymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies about the use of mobile devices for children with SEND dates to 2000 in Turkey (Silman, Yaratan, & Karanfiller, 2017). For instance, a study conducted with parents of children with SEND showed that parents have positive attitudes towards using new tools and mobile applications (Kuzu, Cavkaytar, Odabaşı, Erişti, & Çankaya, 2014).…”
Section: Mobile Education Technologies In Turkeymentioning
confidence: 99%
“…It was underlined that "the software developed as a special education aid is not sufficient for the teaching of different knowledge and skills" (Silman et al, 2017, p.369), which means that applications were not adaptive to individual children's learning differences. For this reason, researchers developed software that can be adapted to different levels and learning speeds of an individual child with SEND (Silman et al, 2017). This software aimed to teach the basic concepts of quantity, width, length, and size.…”
Section: Mobile Education Technologies In Turkeymentioning
confidence: 99%
“…To provide visually-impaired students with better campus life, several studies investigated how assistive technologies can assist such students (Abner & Lahm, 2002;Kamaghe et al, 2020;Kelly, 2009;Kelly & Smith, 2011;Kose & Vasant, 2020;Silman et al, 2017). The inclusion of visually impaired students also sparked interest among researchers about staff and teachers' attitudes and perceptions regarding the inclusion of such students (Herold & Dandolo, 2009;Pearson et al, 2019;Praisner, 2003;Ravenscroft et al, 2019).…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Assistive Technology requires the use of some applications that support the learning cycle. Assistive Technologiesology includes any item that enhances, retains, or revives devices [2].…”
Section: Introductionmentioning
confidence: 99%